2000
DOI: 10.1161/01.cir.102.17.2094
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of Fenestrated Fontan Patients After Closure

Abstract: Background —The late clinical status of Fontan patients after fenestration closure is unknown. Data are now available on all patients who underwent closure from 1989 to 1999. Methods and Results —All patients who underwent catheter closure of a Fontan fenestration were enrolled in either the Clamshell (1989 to 1994) or CardioSEAL (1996 to 1999) regulatory trials. Physiological values obtained at catheterization helped assess the hemodynamic effects of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
0
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(103 citation statements)
references
References 35 publications
4
97
0
2
Order By: Relevance
“…Location, size, and type of fenestrations vary widely. Consequently, numerous devices have been used for fenestration closure, including Gianturco coils [14], detachable coils [20], Raskind duct occluders [13], Clamshell devices [4], CardioSeal devices [17], Amplatzer septal occluder [15,16,22], Amplatzer duct occluder [18], AngelWings devices [19], and covered stents [21]. Choice of device to close a fenestration is guided by several factors, including the type of Fontan circulation (intracardiac versus extracardiac), size and location, geometry of the fenestration, likelihood of placing a long sheath in the systemic atrium, ease of availability and atrial size [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Location, size, and type of fenestrations vary widely. Consequently, numerous devices have been used for fenestration closure, including Gianturco coils [14], detachable coils [20], Raskind duct occluders [13], Clamshell devices [4], CardioSeal devices [17], Amplatzer septal occluder [15,16,22], Amplatzer duct occluder [18], AngelWings devices [19], and covered stents [21]. Choice of device to close a fenestration is guided by several factors, including the type of Fontan circulation (intracardiac versus extracardiac), size and location, geometry of the fenestration, likelihood of placing a long sheath in the systemic atrium, ease of availability and atrial size [21].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of patients had an extracardiac Fontan conduit (n ¼ 63) with only five (n ¼ 5) having lateral tunnel intracardiac conduits. The median size of the fenestration was 5.0 mm (range: 4-6) in a 20 mm (range [14][15][16][17][18][19][20][21][22] conduit. Patients were divided into two groups: The aim in the first group (n ¼ 50) was to obtain complete closure of the fenestration.…”
Section: Methods Patientsmentioning
confidence: 98%
See 1 more Smart Citation
“…Protein-losing enteropathy is also frequently mentioned as occurring after the Fontan operation and in cases of congenital heart diseases, such as tricuspid hypoplasia. 6 However, only a few cases of proteinlosing enteropathy associated with cardiomyopathy have been reported. 7 It is conceivable that severe right-side heart failure induces chronic venous congestion and lymphangiectasia, and, in the present case, abnormal connection of the thoracic duct might have exacerbated lymphangiectasia and induced both protein-losing and poor absorption of fat.…”
Section: Discussionmentioning
confidence: 99%
“…18 Furthermore, multiple centers have shown that a fenestration can be safely closed with a device in the cardiac catheterization laboratory 18 -20 and that such closures are welltolerated. 21 At our institution, we have not routinely occluded fenestrations unless there is significant cyanosis without an alternative cause. Follow-up of this randomized cohort may provide additional insights into effective long-term treatment.…”
Section: Lemler Et Al Fenestrated Fontan Proceduresmentioning
confidence: 99%